Isolated hydatid cyst of spleen: A rare case with rare presentation. (2016) - Kumar, Purushottam; Hasan, Arshad; Kumar, Manoj; Singh, Veena
Highlights: Isolated splenic involvement is very rare. The most important factor in diagnosing splenic hydatid cyst is the awareness of its possibility with these type of presenting complaints. The diagnosis is confirmed by Ultrasound, CECT Abdomen, and Serology(ELISA for ecchinicoccus). Partial or total splenectomy is the treament of choice. Abstract: Hydatid cyst is a common health problem of world in sheep grazing area. Liver is the most commonly involved organ. Splenic hydatid cyst is uncommon and its isolated involvement is very rare. We are presenting a case of isolated hydatid cyst of spleen in a sixty one year old female patient with complaints of pain in the left hypochondrium, dyspepsia and features of gastritis for the last 1 year. The diagnosis was confirmed by Contrast enhanced CT scan (CECT). Laparoscopic splenectomy was performed. The aim of this case report is to emphasize that the most important factor in diagnosing splenic hydatid cyst is the awareness of its possibility and the intraoperative precautions which will decrease morbidity and mortality in the postoperative period.